Phospholipid transfer to high-density lipoprotein (HDL) upon triglyceride lipolysis is directly correlated with HDL-cholesterol levels and is not associated with cardiovascular risk - Ma, Feng; Darabi, Maryam; Lhomme, Marie; Tubeuf, Emilie; Canicio, Aurélie; Brerault, Jean; Medadje, Narcisse; Rached, Fabiana; Lebreton, Sandrine; Frisdal, Eric; Brites, Fernando; Serrano, Carlos; et al. (Atherosclerosis, 2021)
While low concentrations of high-density lipoprotein-cholesterol (HDL-C) represent a well-established cardiovascular risk factor, extremely high HDL-C is paradoxically associated with elevated cardiovascular risk, resulting in the U-shape relationship with cardiovascular disease. Free cholesterol transfer to HDL upon lipolysis of triglyceride-rich lipoproteins (TGRL) was recently reported to underlie this relationship, linking HDL-C to triglyceride metabolism and atherosclerosis. In addition to free cholesterol, other surface components of TGRL, primarily phospholipids, are transferred to HDL during lipolysis. It remains indeterminate as to whether such transfer is linked to HDL-C and cardiovascular disease. When TGRL was labelled with fluorescent phospholipid 1,1′-dioctadecyl-3,3,3′,3′-tetramethylindocarbocyanine perchlorate (DiI), time- and dose-dependent transfer of DiI to HDL was observed upon incubations with lipoprotein lipase (LPL). The capacity of HDL to acquire DiI was decreased by −36% (p<0.001) in low HDL-C patients with acute myocardial infarction (n = 22) and by -95% (p<0.001) in low HDL-C subjects with Tangier disease (n = 7), unchanged in low HDL-C patients with Type 2 diabetes (n = 17) and in subjects with high HDL-C (n = 20), and elevated in subjects with extremely high HDL-C (+11%, p<0.05) relative to healthy normolipidemic controls. Across all the populations combined, HDL capacity to acquire DiI was directly correlated with HDL-C (r = 0.58, p<0.001). No relationship of HDL capacity to acquire DiI with both overall and cardiovascular mortality obtained from epidemiological studies for the mean HDL-C levels observed in the studied populations was obtained. These data indicate that the capacity of HDL to acquire phospholipid from TGRL upon LPL-mediated lipolysis is proportional to HDL-C and does not reflect cardiovascular risk in subjects widely differing in HDL-C levels. [Display omitted] •DiI, a fluorescent phospholipid, was transferred from TGRL to HDL upon lipolysis by LPL in a time- and dose-dependent manner.•HDL capacity to acquire DiI was decreased in low HDL-C patients with acute myocardial infarction and Tangier disease.•HDL capacity to acquire DiI was elevated in subjects with extremely high HDL-C and was correlated with HDL-C.•HDL capacity to acquire DiI was unrelated to overall and CV mortality obtained from epidemiological studies.•HDL capacity to acquire phospholipid from TGRL upon lipolysis by LPL is proportional to HDL-C and is unrelated to CV risk.